Nitrogen, phosphorus, and potassium adsorption and desorption improvement and soil buffering capacity using clinoptilolite zeolite - Palanivell, Perumal; Ahmed, Osumanu Haruna; Omar, Latifah; Abdul Majid, Nik Muhamad (MDPI, 2021)
The physical and chemical properties of clinoptilolite zeolite can be used to enhance soil nutrient availability for optimum crop use. Amending nitrogen, phosphorus, and potassium fertilizers with clinoptilolite zeolite could create a pool of negative charges to retain and release nutrients timely for crop use. Thus, we used clinoptilolite zeolite to enhance Typic Paleudults sorption (adsorption and desorption) of nitrogen, phosphorus, potassium, and this soil’s pH buffering capacity. The treatments evaluated were: (i) 250 g soil alone, (ii) 20 g clinoptilolite zeolite alone, (iii) 250 g soil + 20 g clinoptilolite zeolite, (iv) 250 g soil + 40 g clinoptilolite zeolite, and (v) 250 g soil + 60 g clinoptilolite zeolite. Clinoptilolite zeolite increased soil nitrogen and potassium adsorption, nitrogen desorption, and soil pH. Moreover, ability of the soil to resist drastic change in pH (pH buffering capacity) was improved. Additionally, phosphorus adsorption and desorption of phosphorus and potassium were reduced. Higher potassium adsorption with lower potassium desorption suggests that the clinoptilolite zeolite sorbs potassium effectively. The clinoptilolite zeolite nitrogen, phosphorus, and potassium contributed to the reduction in the adsorption these nutrients. The clinoptilolite zeolite improved nitrogen, phosphorus, and potassium availability and soil buffering capacity to prevent these nutrients from being fixed or lost through for example, leaching. Therefore, clinoptilolite zeolite application could contribute to improved use of nitrogen, phosphorus, and potassium fertilizers to prevent soil, air, and water pollution. Additionally, our intervention could improve nitrogen, phosphorus, and potassium use efficiency.